Contagion Effect Pasar Finansial Antar Negara ASEAN - Wahyuni, Dina Sri; Satria, Doni; Yeniwati, Yeniwati (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
This study aims to determine whether stock price indices influence each other in the ASEAN region and whether there is a contagion effect between financial markets in the ASEAN region. The data used in this research is time series data from January 3, 2017 to December 30, 2021 from the official websitesinvesting.com and wsj.com. This research is a quantitative research using the GARCH analysis model. The results of the study show that stock price indices influence each other in the ASEAN region and there is a contagion effect between financial markets in the ASEAN region